80.1k views
2 votes
Solve the following by completing the square
m² - 10m -13=11
Solve

1 Answer

4 votes

Answer:

m = - 2, m = 12

Explanation:

Given

m² - 10m - 13 = 11 ( add 13 to both sides )

m² - 10m = 24

To complete the square

add ( half the coefficient of the m- term )² to both sides

m² + 2(- 5)m + 25 = 24 + 25, that is

(m - 5)² = 49 ( take the square root of both sides )

m - 5 = ±
√(49) = ± 7 ( add 5 to both sides )

m = 5 ± 7, thus

m = 5 - 7 = - 2 or m = 5 + 7 = 12

User Pitabas Prathal
by
4.8k points